Melawan lewat bahasa: Ujaran performatif tokoh marginal dalam Pasung Jiwa dan Kerumunan Terakhir - Ayunda Nuril Chodiyah; Setya Yuwana Sudikan; Ririe Rengganis (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
The purpose of this study is to examine the utterances of marginalized characters in Okky Madasari’s Pasung Jiwa and Kerumunan Terakhir as performative acts containing resistance to dominant social structures. This research is a qualitative descriptive type with a feminist approach. The research data consists of narrative excerpts, monologues, and dialogues containing performative utterances. Data collection was carried out through intensive reading. The analysis focused on how these utterances form performative acts in the character’s social context, and function as discursive practices that reproduce or challenge norms of identity and power. The results of the study show that language is not merely an expression of personal experience, but a form of performative act that contains resistance to dominant social structures. The language in the characters’ utterances can be used as a means to restructure the social order. Through the concept of linguistic performativity by Austin and Butler, the language spoken by the characters is present as a tool for negotiating meaning and power. Language becomes a space of resistance that challenges the boundaries of social norms, challenges the truth claims conveyed by the majority, and invites readers to see reality from other perspectives that tend to be marginalized.